2013
DOI: 10.4236/snl.2013.34a012
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Boron-Nitrogen Substitued Graphene Nanoribbon with Nucleobases: The Idea of Biosensor

Abstract: In this paper we have designed a biosensor device built from B-N substituted graphene nanoribbon within density functional based tight-binding (DFTB) framework. We have investigated the interaction of the nucleobases adenine (A), Guanine (G), Cytosine (C) and Thymine (T) with device. Our calculation suggests that all the nucleobases have different interaction strength when they interact with device and shows that guanine has stronger interaction with device than other nucleobases. It reveals that the absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…42 The graphene nanoribbon doped with boron-nitrogen has exhibited different transmission signals for the NBs. 43 In addition to graphene, the theoretical study on the interaction of NBs with silicene (silicon as reactive center) has revealed that it can be useful for DNA sequencing. 44 The adsorption strength of NBs with the surface of silicene is governed by SiÁ Á ÁH (non-covalent) and SiÁ Á ÁO (partial covalent) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…42 The graphene nanoribbon doped with boron-nitrogen has exhibited different transmission signals for the NBs. 43 In addition to graphene, the theoretical study on the interaction of NBs with silicene (silicon as reactive center) has revealed that it can be useful for DNA sequencing. 44 The adsorption strength of NBs with the surface of silicene is governed by SiÁ Á ÁH (non-covalent) and SiÁ Á ÁO (partial covalent) interactions.…”
Section: Introductionmentioning
confidence: 99%